Cardiac Rhythm Management Pacing, Ablation, Devices - Min, Mart; Cismaru, Gabriel (IntechOpen, 2022)
Many methods, techniques, and tools have been developed and successfully applied to stabilize and control heart rate. Modern implantable devices (pacemakers, defibrillators, tools for continuous monitoring and resynchronization therapy) and treatment methods, including minimally invasive surgery (ablation, implantation), have been developed for managing cardiac rhythm and avoiding heart failure. In addition to electrical pacing, ablation is an effective minimally invasive surgical method for reducing and blocking arrhythmic phenomena, both as an independent treatment method or in conjunction with pacing therapy. This book discusses modern cardiac rhythm management methods and devices as well as some important medical aspects of their use.